Isolation and Characterization of New Antibiotics from Indonesian Coastal Marine Bacteria - VERONICA VERONICA; BIBIANA W LAY; STELLA MAGDALENA (Microbiology Indonesia, 2014)
Antibiotics are organic compounds produced by various microorganisms and have the ability to inhibit the growth or kill other microorganisms. However, the irrational application of antibiotics lead to resistance of microorganisms so that they become ineffective. The objectives of this study were to isolate and characterize new antibiotics from Indonesian coastal marine bacteria. In this study, a total of 141 isolates consisting of seven Streptomyces sp. isolates and 134 isolates of other marine bacteria, were obtained from Indonesian coastal regions. Based on antimicrobial activity assay, four Streptomyces sp. and five marine bacteria isolates showed antimicrobial activity towards Bacillus cereus and Staphylococcus aureus with the diameter of inhibition of 3-12 mm. Further, antimicrobial compounds were produced successfully extracted with six organic solvents, such as 1-butanol, dichloromethane, n-hexane, chloroform, and toluene. The best solvent to extract antimicrobial compounds from Streptomyces sp. isolates was 1-butanol, while the best solvent to extract antimicrobial compounds from other marine bacteria isolates could not be specified. Antimicrobial compounds were successfully separated by thin layer chromatography with mobile phase used were 1-butanol, acetic acid, and water at a ratio of 4:1:2 and retention values obtained at 0.50 and 0.63.